Panel Data Regression to Analyze the Impact of Accounting Automation on Cost Efficiency in Service Companies - Lestari, Rahma; Pratama, Andika (Universitas Sains dan Teknologi Komputer, 2026)
The evolution of digital tech has completely transformed traditional ways of working in the accounting field, making accounting automation a primary tool for reducing expenses and increasing operational efficiency. The use of RPA, cloud accounting, and AI is fundamental to cost-performance optimization for service organizations that rely primarily on the speed and precision of information. The present research aspires to make an empirical investigation into the effect of accounting automation on the cost efficiency of service firms in Indonesia. The examination is conducted using a fixed-effects panel data regression model (Fixed Effects Model) with 240 observations from 40 service firms for the period 2018–2023. The analysis shows that accounting automation is positively and significantly correlated with cost efficiency (coefficient = 0.283; p < 0.05). On the other hand, firm size and digitalization have a positive impact, but leverage still does not significantly affect the result. The overall effect of the independent variables on the dependent variable is very strong, as indicated by an R² of 0.712. The research is innovative in several ways, including the use of panel data to uncover the long-term effects of automation and the application of TCE and TAM theories to cost efficiency. The results support the idea that accounting automation is not only a technological change but also a powerful management strategy for improving cost efficiency and enhancing the competitiveness of service firms in the digital era.